Relation between Married Couple in Indonesian Islamic Marriage Law Perspective Human Right International Instrument - M. Faiz Nashrullah; Dery Ariswanto; Ezra Junsevo Budiawan (AHKAM, 2025)
Indonesia's Islamic marriage law, established in 1974 and partially revised in 2019, is increasingly viewed as outdated, particularly in its regulation of spousal relationships. While the 2019 amendment addressed the legal age of marriage, other substantive aspects, especially those governing the relationship between husband and wife remain misaligned with international human rights standards. This study aims to analyze the provisions governing marital relations in Indonesia’s Islamic marriage law through the lens of international human rights instruments. Adopting a qualitative, literature-based research design, the study utilizes legislative and conceptual approaches, with a specific focus on the principle of justice as articulated in global human rights frameworks. The findings indicate that, although Indonesia’s Islamic marriage law has incorporated several principles consistent with human rights norms, it still contains provisions that perpetuate gender-based disparities. These include the formal designation of the husband as the head of the household and the wife as a homemaker, as well as imbalances in rights and responsibilities that reflect patriarchal assumptions. Such legal constructs not only conflict with gender equality but also undermine Indonesia's commitments to international human rights obligations. The study concludes by recommending further legal reform to harmonize Islamic marriage law with contemporary understandings of gender justice and human rights.